1998
DOI: 10.1074/jbc.273.2.849
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Mechanisms of Action of the Saccharomyces cerevisiae Dominant Lethal cdc42 G12V and Dominant Negative cdc42 D118A Mutations

Abstract: The Saccharomyces cerevisiae Cdc42p GTPase is localized to the plasma membrane and involved in signal transduction mechanisms controlling cell polarity. The mechanisms of action of the dominant negative cdc42 D118A mutant and the lethal, gain of function cdc42 G12V mutant were examined. Cdc42 D118A,C188S p and its guanine-nucleotide exchange factor Cdc24p displayed a temperature-dependent interaction in the twohybrid system, which correlated with the temperature dependence of the cdc42 D118A phenotype and supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
53
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(56 citation statements)
references
References 69 publications
(89 reference statements)
2
53
1
Order By: Relevance
“…These data suggest that the kinase domain of Skm1 can potentially phosphorylate at least some of the same substrates as Ste20, but that, in the context of the full-length protein, is unable or unavailable to do so (Martin et al, 1997). Interestingly, the lethal effects of expressing activated Cdc42 in budding yeast can be suppressed by deletion of CLA4 or SKM1, but not by deletion of STE20 (Davis et al, 1998). These results suggest that, like the other two yeast Paks, Skm1 is a bona-fide effector of Cdc42, but its precise role remains for the moment obscure.…”
Section: Skm1mentioning
confidence: 72%
“…These data suggest that the kinase domain of Skm1 can potentially phosphorylate at least some of the same substrates as Ste20, but that, in the context of the full-length protein, is unable or unavailable to do so (Martin et al, 1997). Interestingly, the lethal effects of expressing activated Cdc42 in budding yeast can be suppressed by deletion of CLA4 or SKM1, but not by deletion of STE20 (Davis et al, 1998). These results suggest that, like the other two yeast Paks, Skm1 is a bona-fide effector of Cdc42, but its precise role remains for the moment obscure.…”
Section: Skm1mentioning
confidence: 72%
“…The D123A mutation is located in a conserved position that, when mutated in other small GTPases, results in a dominant-negative phenotype, whereas the G18V mutation in small GTPases (including RAC homologs) gives rise to a dominant-activated phenotype because the mutant protein is unable to hydrolyse GTP and constitutively interacts with downstream effectors (Davis et al, 1998;Fanto et al, 2000;Kawaski et al, 1999;Kost et al, 1999). Both mutant alleles, as well as a wild-type allele were placed behind the ethanolinducible alcA promoter from A. nidulans (May, 1987).…”
Section: Expression Of Cflbmentioning
confidence: 99%
“…Mutational and biochemical characterization of Cdc42p revealed that regulation of the guanine nucleotide state of Cdc42p is essential for its proper function in these processes (9,40). Moreover, biochemical and two-hybrid studies showed that GTP-bound Cdc42 G12V p displayed enhanced interactions with effectors and regulators (4, 5, 8-10, 15, 20, 29, 30, 33, 37).…”
mentioning
confidence: 99%
“…Mutational analysis of the Cdc42p effector domain, which consists of amino acids 26 to 50 ( Fig. 1), indicated that this region is required for function and lends specificity to interactions with a number of Cdc42p regulators and effectors (9,23,33). However, how these various specific interactions lead to downstream events such as actin reorganization and bud emergence still needs to be explored.…”
mentioning
confidence: 99%
See 1 more Smart Citation